Analisis Hubungan Rasio Debit dan Penggunaan Lahan di DAS Sekampung Hulu dengan Menggunakan Model SWAT dan Regresi Linier Berganda - Pratiwi, Reysa Fattah; Ridwan, Ridwan; Amin, Muhammad; Triyono, Sugeng (abe.fp.unila.ac.id, 2022)
Watershed of upper Way Sekampung system is one of watershed area located in Tanggamus Regency, Lampung Province with the large of 43.453,30 Ha. Watershed of Upper Way Sekampung system had been changing from forest land to largest land of agriculture. The purpose of this research was to find out the parameter effected to discharge in watershed of Upper Sekampung system, to find out the correlation model of various land use in multiple linear with discharge ratio of SWAT, and to find out the land use is most effective (sensitive) to ddischarge ratio. The method of this research is preparation and data collecting. The analysis in this research is using the SWAT analysis, multiple linear regression analysis, error level analysis (RMSE), dan sensitivity tests model analysis. So it can be concule that 1) The coefficient parameter of surface flow, manning’s constanta of land use and river surface, compensation factor of evaporation of land surfaces, compensation factor for plant transpiration, coefficient of water plant loss, flow of water soil factor (day), hydrolic conductivity flow of river, and water storage capacity (mm/mm) was affected to discharge at watershed of Upper Sekampung system with precision levels (validity) of 82%. 2) hidrology condition (discharge) at watershed of Upper Sekampung system also it can be using by exponential regression model that correlation between the exponential ratio (Q unit m3/s) with the area of each land use (hectare unit), with coefficient determidation value of 0,324. 3) The land’s use most influential (sensitive) increasing discharge rasio value is ratification is secondary farm (PLKR), while the land’s use most influential (sensitive) decreasing discharge rasio value is schrub (SMBL).